Inducing corporate social responsibility: should investors reward the responsible or punish the irresponsible? - Mackey, Tyson B. (Journal of business ethics, 2022)
Investors with a pro-social or sustainability agenda increasingly attempt to influence firm managers to adopt socially responsible behavior, either through positive/reward tactics or negative/punishment tactics. This paper considers how investors can use each approach to differentially influence managers to make more CSR investments. The paper uses game theory with an all-pay contest structure to model how a large institutional investor could reward firms for CSR activities by creating a socially responsible investment fund (reward contest) or punish firms via shareholder activism (punishment contest). We identify conditions under which the punishment contest induces a higher level of CSR activity among firms compared to the reward contest. Managers bearing substantial private costs stemming from the activism is one such condition. Spillover effects are seen as the other managers in the economy engage in CSR to avoid being punished by the investor's activism. This level of engagement is not the case when rewards are used - only those managers with an expectation of being rewarded increase their CSR activity in that scenario. This suggests, for example, that incorporating thresholds or tiers (e.g. gold, silver, and bronze-level winners) can increase the effectiveness of reward contests. Implications for designing both positive and negative CSR inducements are explored. We also identify the ethical dilemmas that relate to such influence attempts.